2005
DOI: 10.1097/01.psy.0000174169.14227.1f
|View full text |Cite
|
Sign up to set email alerts
|

Does Panic Disorder Increase the Risk of Coronary Heart Disease? A Cohort Study of a National Managed Care Database

Abstract: The risk of CHD associated with a diagnosis of PD suggests the need for cardiologists and internists to monitor panic disorder to ensure a reduction in the risk of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 43 publications
0
39
2
1
Order By: Relevance
“…As discussed in section 5.2.2. we might suspect that the majority of baseline PD patients were in an early phase of the disease and therefore had lower rates of co-morbid psychiatric disorders than is usually seen in PD patients in psychiatric clinics. A higher rate of co-morbid depression might have contributed to the development of CAD in more patients as co-morbid depression increased the risk for subsequent cardiac events in a cohort study of PD (85). The mean age of the patients was higher than reported in most studies of PD in psychiatric settings.…”
Section: External Validitycontrasting
confidence: 40%
See 1 more Smart Citation
“…As discussed in section 5.2.2. we might suspect that the majority of baseline PD patients were in an early phase of the disease and therefore had lower rates of co-morbid psychiatric disorders than is usually seen in PD patients in psychiatric clinics. A higher rate of co-morbid depression might have contributed to the development of CAD in more patients as co-morbid depression increased the risk for subsequent cardiac events in a cohort study of PD (85). The mean age of the patients was higher than reported in most studies of PD in psychiatric settings.…”
Section: External Validitycontrasting
confidence: 40%
“…However, an extensive review published in 1998 concluded that studies of associations between PD, CAD, and cardiovascular mortality suffer from serious methodological limitations, such as the lack of sound methodological assessment of PD and prospective design (84). Since then, a recently published cohort study of nearly 40.000 persons diagnosed with PD reported that having a PD diagnosis almost doubled the risk for subsequent CAD (85).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Other research has found the presence of anxiety symptoms to be a risk factor for the development of future coronary heart disease. [118] A prospective study of risk for coronary heart disease (CHD) among male veterans (M 5 59.6) found that for each standard deviation of symptom increase, on the Mississippi Scale for Combat-Related PTSD or the Keane PTSD scale, a significant increase in risk for nonfatal myocardial infarction, angina, and fatal CHD was observed. [119] These findings provide evidence that PTSD symptoms may increase the risk for CHD in older men.…”
Section: Comorbidity and Differential Diagnosismentioning
confidence: 99%
“…In this regard, a study, which assessed a total of 39 920 panic disorder (PD) patients and an equal number of patients without PD, showed that PD patients had a 2-fold increased risk of CHD in the prospective follow-ups (hazard ratio (HR), 1.87; 95% CI, 1.80 -1.91). Also, after controlling for the covariates, PD patients with depression were nearly 3 times more likely to develop CHD (HR, 2.60; 95% CI, 2.30 -3.01) (10).…”
Section: Anxiety As An Etiological Factor For Chdmentioning
confidence: 99%